A fotgrafia e a obra pública em Portugal. O registo do processo de obra na invenção da urbanidade e na afirmação da modernidade - Mesquita, M. J. F. (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
This text proceeds to an approach to the public work photography in Portugal, focusing the discussion on the work process registration, often covered with a deep invisibility and lack of notoriety. In the period between centuries (XIX/XX) – when conditions of the "urban being" and urbanity were strongly discussed – the times and methods to make space (City and Territorial ones) would tell with photography as a valuable ally, contributing itself, as a result of its development in the spheres of art and technology and profusion of use, to the progress of the concept of urbanity. Between “official photography” and photography considered as a tool of great procedural value, public work, in charge of the various levels (central and local) of the States that emerged at the end of that between centuries (after the defeat of the Liberal State several projects in Europe), revealed to know how to use it. At this, some of them, such as Portugal, would know how to last in time and space, knowing to deal with the issues of image: certifying mastery over their projections and representations, crucial to the process of invention of new identities then in progress. Opposing to the wide road of oblivion, I here throw the defy on the need for reflection on the relationships between the spread of photography use and the development of the process/project/performance of public work, in Portugal, in the above mentioned period, assuming an increasingly perspective of interdisciplinary on the discussion.